2022
DOI: 10.3390/w14030325
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land-Use Change, Associated Land-Use Area and Runoff on Watershed Sediment Yield: Implications from the Kaduna Watershed

Abstract: An uncontrolled sediment influx from the watershed upstream is a known threat to dam stability, while the pattern and amount of sediment yield are influenced by the predominant upstream land-use and land cover (LULC) types, precipitation amount, and intensity. Hence, the need to monitor sediment yield accumulation and its controlling factors in dam operation becomes crucial. In this paper, the Soil and Water Assessment Tool (SWAT) was used to assess the roles of land-use change, land cover area, and runoff on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
1
13
0
1
Order By: Relevance
“…The watershed hydrological processes were quantified using the SWAT model (Table 5); the analysis result revealed that precipitation has continued to decrease since 1975 to about 4.2% in 2013. The prediction agrees with Daramola et al, 2022;Bello et al, 2012;Mohammed, 2014;Odjugo, 2005;Ogilvie et al, 2010;Nicholson, 2013;Idowu et al, 2011;Fasona and Omojola, 2005;Mahé and Olivry, 1999;Abaje et al, 2010;Mahe et al, 2013). Similarly, Aigbe and Oluku (2012) connected the extinction of forest cover in Nigeria to a constant reduction in rainfall.…”
Section: Climate Variation and Impact On Water Balance And Water Yieldsupporting
confidence: 71%
See 3 more Smart Citations
“…The watershed hydrological processes were quantified using the SWAT model (Table 5); the analysis result revealed that precipitation has continued to decrease since 1975 to about 4.2% in 2013. The prediction agrees with Daramola et al, 2022;Bello et al, 2012;Mohammed, 2014;Odjugo, 2005;Ogilvie et al, 2010;Nicholson, 2013;Idowu et al, 2011;Fasona and Omojola, 2005;Mahé and Olivry, 1999;Abaje et al, 2010;Mahe et al, 2013). Similarly, Aigbe and Oluku (2012) connected the extinction of forest cover in Nigeria to a constant reduction in rainfall.…”
Section: Climate Variation and Impact On Water Balance And Water Yieldsupporting
confidence: 71%
“…Abbaspour et al, (2015) explained that these uncertainties are expected in a large watershed. Thus, a large watershed as large as the Kaduna watershed will experience all these uncertainties that may be largely responsible for the high r-factor prediction (Daramola et al, 2022). However, the general statistical evaluation performance of the model using Nash-Sutcliff, coefficient of determination, p-factor, and r-factor shows that the prediction is within the suitable standards (Moriasi et al, 2007;Krause et al, 2005;Motovilov et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of GIS tools and remote sensing have led to a new model in environmental studies (Chukwudi et al, 2017). Remote sensing and GIS have been extensively accepted in environmental resources management and widely applied in landuse and landcover change detection (Overmars et al, 2007;Pontius et al, 2001;Mas et al, 2014) and land classifications as well (Feranec, 2000;Lambin, 1997;Heymann, 1994;Ahmed et al, 2018;Daramola et al, 2022).…”
Section: Introductionmentioning
confidence: 99%